Nurses' turnover intention, hope and career identity: the mediating role of job satisfaction - Huiling Hu; Chongkun Wang; Yue Lan; Xue Wu (BMC, 2022)
Abstract Background A high turnover rate has become a critical issue in the field of nursing and how to tackle the problem of nursing turnover has received increased attention worldwide. Hope, career identity, job satisfaction may be useful for reducing turnover. The aim of this study is to explore the relationships among career identity, hope, job satisfaction, and the turnover intention of nurses, and to test the mediating role of job satisfaction on the associations of hope and career identity with turnover intention. Methods A descriptive cross-sectional design was used. A total of 500 nurses were recruited from five comprehensive tertiary hospitals using convenience sampling. The questionnaire included items about sociodemographic information as well as the Adult Dispositional Hope Scale, Nursing Career Identity Scale, Job Satisfaction Index Scale, and Nurse Turnover Intention Scale. Pearson's correlation, multiple linear regression, and structural equation modeling were used to analyze the data. We describe the study in accordance with the STROBE statement. Results Hope (r = − 0.227, p < 0.001) and career identity (r = − 0.342, p < 0.001) were negatively correlated with turnover intention. Job satisfaction played a completely mediating role on the associations of hope and career identity with turnover intention (β1 = − 0.09, β2 = − 0.33). Conclusions Job satisfaction mediated the associations of career identity and hope with turnover intention. Thus, effective measures can be taken to enhance nurses' hope and career identity in order to improve their job satisfaction and thereby reduce their turnover intention. Providing nurses with more support, helping them find a spiritual foundation, and holding mindful activities that stimulate positive emotions are helpful. In addition, colleges should pay more attention to instilling nursing students with career identity and nursing values.